Replication and Analysis of the Fama-French Three-Factor Model: Evidence from the Hong Kong Stock Market - Asty Khairi Inayah Syahwani; Elisabeth Simanjuntak; Tiya Octaviani (ACCOUNT: Jurnal Akuntansi, Keuangan dan Perbankan, 2026)
This study aims to examine whether the Fama-French Three-Factor Model can explain stock returns in the Hong Kong stock market, while also testing the robustness of the model beyond its original United States context. Using secondary data from all companies listed on the Hong Kong Stock Exchange for the period July 2021 to June 2024, the study constructs three key factors, namely market risk premium, firm size (SMB), and firm value (HML), which are subsequently analyzed through multiple regression analysis across varying market conditions and sectors. The findings reveal that all three factors carry significant explanatory power over stock returns across sectors in the Hong Kong market. Among the three, the size factor (SMB) demonstrates the strongest influence, suggesting that firm size plays a particularly important role in explaining return differences within the Hong Kong market. Furthermore, the model proves to be more effective in explaining return variability among large firms with high book-to-market ratios than among small firms. Despite these findings, the study acknowledges certain limitations, most notably its relatively short time horizon and its focus on a single market, which may restrict the generalizability of the results to other markets or longer time periods. Nonetheless, this study makes a meaningful contribution to the asset pricing literature by providing empirical evidence on the application of the Fama-French Three-Factor Model in an international market setting, offering valuable insights for academics, investors, portfolio managers, and policymakers, particularly those operating in Hong Kong and economies with similar market characteristics.